RAD51B plays an essential role during somatic and meiotic recombination in Physcomitrella. Issue 19 (26th September 2014) - Charlot, Florence; Chelysheva, Liudmila; Kamisugi, Yasuko; Vrielynck, Nathalie; Guyon, Anouchka; Epert, Aline; Guin, Sylvia Le; Schaefer, Didier G.; Cuming, Andrew C.; Grelon, Mathilde; Nogué, Fabien
Abstract: The eukaryotic RecA homologue Rad51 is a key factor in homologous recombination and recombinational repair. Rad51-like proteins have been identified in yeast (Rad55, Rad57 and Dmc1), plants and vertebrates (RAD51B, RAD51C, RAD51D, XRCC2, XRCC3 and DMC1). RAD51 and DMC1 are the strand-exchange proteins forming a nucleofilament for strand invasion, however, the function of the paralogues in the process of homologous recombination is less clear. In yeast the two Rad51 paralogues, Rad55 and Rad57, have been shown to be involved in somatic and meiotic HR and they are essential to the formation of the Rad51/DNA nucleofilament counterbalancing the anti-recombinase activity of the SRS2 helicase. Here, we examined the role of RAD51B in the model bryophyte Physcomitrella patens . Mutant analysis shows that RAD51B is essential for the maintenance of genome integrity, for resistance to DNA damaging agents and for gene targeting. Furthermore, we set up methods to investigate meiosis in Physcomitrella and we demonstrate that the RAD51B protein is essential for meiotic homologous recombination. Finally, we show that all these functions are independent of the SRS2 anti-recombinase protein, which is in striking contrast to what is found in budding yeast where the RAD51 paralogues are fully dependent on the SRS2 anti-recombinase function.